(untitled) (Quaestiones Disputatae: temas en debate, 2022)
The study of the violation of children’s rights has been widely scaled up in a variety of fields, from educational to social. However, it has mainly focused on explaining the consequences and causes of rights violations. This research, on the other hand, has been interested in understanding the meanings that students have about the violation of their rights. Therefore, from a qualitative study, the information gathered in the interviews was categorised under the categories of violation, protection, environment and support and communication networks, which are analysed from the constructionist theory. This research was done to try to demonstrate that social relations in the school and family environments delimit the conceptions that children have about the violation of their rights, which are associated both with the environment and with individuals, the negligence of institutions and the concrete actions of physical mistreatment.